Employment Discrimination: An Organizational Model - Haberfeld, Yitchak (Academy of Management Journal, 1992)
Empirical findings have indicated that gender-based discrimination is manifested during the assignment of workers to organizational positions. Since the position occupied has a major effect on a worker's salary, discriminatory processes in assigning positions should be incorporated into a salary discrimination model. Organizational variables were more important than individual variables in explaining both legitimate salary differentials between the men and women studied and gender-based salary discrimination.